12‐Tungstosilicic Acid H4[W12SiO40] Over Natural Bentonite as a Heterogeneous Catalyst for the Synthesis of 3, 4‐dihydropyrimidin‐2(1H)‐Ones. Issue 8 (24th February 2020) - V Chopda, Lakha; Dave, Pragnesh N.
Abstract: Regionally available bentonite was modified by using heteropolyacid 12‐tungstosilicic acid H4 [W12 SiO40 ] (TSA). The prepared 10–30 % TSA/bent catalysts were characterized by XRD, FTIR, FeSEM and EDS. The catalytic activity of all three samples was studied on classical Biginelli reaction. Among all, 30 % TSA/bent displayed high catalytic activity and reusability. The effect of solvent was also undertaken to find the best media for the reaction. This protocol was extended to various aldehydes for the synthesis of different dihydropyrimidones (DHPMs) in high yields in ethanol. Abstract : 10 %, 20 % and 30 % tungstosilic acid (TSA) were supported over bentonite clay. The catalysts are well characterized by x (XRD), FT‐IR, field FeSEM and EDS. All charactization method revealed that TSA was supported over bentonite. The prepared catalysts were tested for classical Biginelli reaction for synthesis dihydropyrimiodones. Among the used catalysts, 30 % TSA/bent displayed high yield of product towards model Biginelli reaction between benzaldehyde, ethylacetoacetate and urea in ethanol. 30 % TSA/bent showed good yield of product in DMF and solvent free condition.